Reduction in Infrastructure and operating costs using Server Virtualization (International Journal of Engineering and Computer Science, 2016)
This paper presents a brief look at virtualization, and its benefits  in today’s  IT world.  Server Virtualization results in overall reduction in infrastructure and operating costs, manpower requirements, space. Virtualization provides benefits  such as greater efficiency in CPU utilization, better management through central environment control, reduced project timelines, improved disaster recovery capability, more central control of the desktop, and also improved outsourcing services.